A comparison of photo-taking and online-sharing behaviors of mainland Chinese and Western theme park visitors based on generation membership - Prideaux, Bruce; Lee, Louisa Yee-Sum; Tsang, Nelson (Journal of vacation marketing, 2018)
This research investigates and compares the photo-taking and online photo-sharing behaviors of mainland Chinese and Western theme park visitors using decade length generations. Given the rapid growth in digital photography and growing popularity of online sharing of photos, an enhanced understanding of the photo-taking and photo-sharing behaviors of visitors based on generation membership will assist theme park managers develop new social media marketing strategies. Most previous research has employed Western definitions of generations such as baby boomer, generation X, and generation Y. These definitions do not always apply in non-Western settings indicating the need for an alternative approach. This study uses a decade length definition of generations: the post-70s, post-80s, and post-90s. Results of the survey found that photo taking and online photo sharing are very popular but do vary between generations and cultures. For example, mobile phones were found to be the most popular photographic equipment for mainland Chinese and the least popular for post-90s Western respondents. All generations rated family/friend, landscape, and selfies as the top three areas of photo content. Selfies were twice as popular with mainland Chinese post-90s as their Western counterparts in the same generation. The findings highlight the usefulness of decade length generations and of identifying photo-taking and photo-sharing activities based on cultural groupings. The findings also indicated opportunities for co-creation at least in the area of photo taking in a theme park setting.